(3GdfhQ GdSGWY aj faj GdMQL Yf GdLGeYs - (3jMji Hf CMeO Hf YhGV, GHf YhGV,J (B1106 (3g` s ((3eMeO Hf bGSe Hf SdjeGf Hf eMeO GdNjGW s)
(3ChdgG (B:s
(3GdMeO ddg GdPi jSQ hNaaa hQNU heG YSQ hdG MQL hHYO abO ENJda ai GdLeY Hfj UdGJi GdYUQjf hGdYTGFjf JbOjekG h`GNjQkG dZjQ YPQ s
(3BNQgG (B:s
(3jJQLM Cf GdJhbjJ SfI eDcOI , hCf GdLeY hGdJCNjQ HdG JgGhf LGFRceG MceJ HPdc GdCOdI GdeajOI GfJgi s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3fSNI eUMMIs
(3YdiWQJgG bQGAI hSeGY Ydi GdeDda deMeO Hf bGSe GdNjGW GdfGSN hcPG Ydi GdZGTjI s
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
Keywords: (3Gdabg GdESdGejs